Optimalisasi Pengawasan dan Penertiban Petugas Apron Movement Control Guna Meningkatkan Keamanan di Bandar Udara Internasional Komodo Labuan Bajo - Imam Sutan Maulana; Septiyani Putri Astutik (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the optimization efforts made by the Apron Movement Control (AMC) unit in supervising and regulating the movement of people and vehicles in the airside area of ​​Komodo International Airport, Labuan Bajo. The AMC unit is responsible for managing the movement of aircraft, people, and vehicles, including plotting parking stands, arranging ground handling, administering flight data, licensing airside vehicles, supervising engine run-up, apron cleanliness, and handling fuel spills. Supervision is carried out based on SOP, but in emergency situations such as aircraft skidding or unloading on the taxiway, the AMC must be able to adapt quickly to relevant safety procedures. This study uses a qualitative method with direct observation techniques, interviews with three AMC personnel, as well as SOP documentation and incident reports. The results show that the implementation of supervision and control has been running according to PM-IK standards. The focus of supervision includes aircraft movement, engine idle, GSE vehicle speed, completeness of worker PPE, and passenger arrangements to the aircraft. However, the main obstacle is the limited personnel which causes a high workload and supervision is not optimal, so that violations by service users or workers still occur and have the potential to endanger flight safety.